A free-standing Li4Ti5O12/graphene foam composite as anode material for Li-ion hybrid supercapacitor. (20th December 2017) - Qian, Yao; Cai, Xiaoyi; Zhang, Chunyan; Jiang, Haifeng; Zhou, Lijun; Li, Baosheng; Lai, Linfei
Abstract: The demand of highly efficient energy storage system has significantly increased along with the rapid development of electric vehicles and hybrid electric vehicles. However, the energy and power density of standard energy storage devices, such as Li-ion batteries or supercapacitors still cannot meet the requirement of the state-of-the-art electric vehicles. Herein, free-standing Li4 Ti5 O12 /graphene foam (LTO/GF) composite is synthesized via a hydrothermal method, and applied as anode material for Li-ion hybrid supercapacitor. The as-synthesized LTO/GF delivers specific capacities of 186, 179 and 175 mAh g −1 at 0.2, 0.5 and 1 C, respectively. Li-ion hybrid supercapacitors have been assembled with LTO/GF as anodes and activated carbon as cathodes, which have energy densities of 46 and 26 Wh kg −1 at power densities of 625 and 2500 W kg −1, respectively. Furthermore, the hybrid supercapacitor exhibits a superior cycle performance with capacity retention of 83% after 4000 cycles at 1 A g −1 . GF sponge substrate can speed up ions and electrons transport with short diffusion lengths and large electrode/electrolyte contact area. Hierarchically structured LTO/GF electrode is lightweight, flexible, and is promising for energy storage applications.